Patrimoni di destinazione e responsabilità patrimoniale - Ferroni, Lanfranco (Cultura giuridica e diritto vivente, 2014)
[Patrimony of Affectation and Patrimonial Liability] The study aims to offer a restrictive interpretation of the provision contained in art. 2645 ter of the Civil Code. It limits the possibility of creating separate patrimonies or patrimonies whose only purpose is to serve social or supraindividual needs. This interpretation proves to be more in line with the principle of unlimited and universal patrimonial responsibility, as still fully existent in the Italian law. It also consistent with the need to avoid any abusive use of patrimonial separation which may lead to undue limitations of liability.